PERAN KELEMBAGAAN SOSIAL DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT MELALUI INOVASI PROGRAM RASAILAHDAKU DI KOTA PADANG - Imam Pujima Jailani Hasibuan; Fari Rahma; Fina Jantika Putri; Rona Jauza; Siti Fazira Aranda (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2023)
The RASAILAHDAKU program is an innovative program that aims to improve people's welfare through the use of social institutions. This program is implemented in the city of Padang, which is the capital of the province of West Sumatra in Indonesia. The background of this program is the need to overcome the problem of poverty and social inequality in the city of Padang. Even though this city has great economic potential, there are still many people who live below the poverty line and do not have adequate access to the resources needed to improve their welfare. Researchers will describe the information and research findings related to the Implementation of the Rasailah Daku Program for Street Children in the City of Padang, using the results of the information and findings from the process of observation, interviews and library research. The data and results of the research will be broken down into 2 parts of the review, namely the process of the feel me program as a prosecution of street children and the results of the feel me program. In the RASAILAHDAKU program for the further development of street children in the city of Padang, there is an important role for various social institutions. These institutions work together in order to provide guidance, protection and services to street children in order to improve their quality of life. The expected results of this program are reducing the number of street children who are involved in wrong associations, increasing the value of social solidarity and a sense of child nationalism, as well as increasing the knowledge and skills of children as the next generation.